Evaluasi Kebijakan Ruang Terbuka Hijau (RTH) Publik Di Provinsi Jawa Timur : Systematic Literature Review - Viandi Pramulia (Jurnal Cahaya Edukasi, 2026)
This study evaluates the implementation of public Green Open Space (RTH) policies in East Java Province by employing William N. Dunn’s policy evaluation theory as the primary analytical framework. Five case studies were examined: Herbal Village Nginden Surabaya, Green Open Space in Kebomas District Gresik, Suroboyo Park Surabaya, Tanjung Puri Park Sidoarjo, and Aloon-Aloon Madiun. Using Dunn’s six evaluation criteria effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness the findings reveal significant variations in policy performance across regions. Surabaya demonstrates stronger outcomes on most indicators, while Gresik, Sidoarjo, and Madiun face constraints related to limited facilities, mismatches with spatial planning, and low community participation. The results confirm that Dunn’s framework effectively identifies the strengths and weaknesses of RTH policies and underscores the need for enhanced institutional capacity, consistent spatial planning, and increased community involvement to achieve sustainable RTH management in East Java.